Contraction-Expansion and the Effects on the Aquiferous System in the Demosponge Halichondria panicea - Goldstein, Josephine; Bisbo, Nicklas; Funch, Peter; Riisgård, Hans Ulrik (Frontiers in Marine Science, 2020)
Contractile behavior is common among sponges despite their lack of nerves and muscles. As sessile filter-feeders, sponges rely on water with suspended food particles being pumped through their aquiferous system. During contractions, however, the water flow is being reduced and eventually shut down. Yet, purpose and underlying pathways of contractile behavior have remained largely unclear. Here we document the external and internal morphology of contracted and expanded single-osculum explants of the demosponge Halichondria panicea. We show that contraction-expansion dynamics can occur spontaneously (in untreated explants) and can be induced by exposure to chemical messengers such as -aminobutyric acid (GABA, 1 mM) and L-glutamate (L-Glu, 1 mM), or to inedible ink particles (4 mg L-1). The neurotransmitter GABA triggered similar contraction-expansion dynamics in H. panicea as observed in untreated explants. The effects of GABA-induced contraction-expansion events on the aquiferous system were investigated using scanning electron microscopy (SEM) on cryofractured explants. Our findings suggest that contraction-expansion affects the entire aquiferous system of H. panicea, including osculum, ostia, in- and excurrent canals and apopyles.